Effectiveness of Constructivism Approach to Increase Mathematical Communication Skill of Students Junior High School - Hadijah Hadijah (UIN Antasari, 2018)
The purpose of this study was to analyze and explore the effectiveness of constructivism approaches in improving mathematical communication skills of junior high school students in the city of Paser. The experimental quasi method was used in this study to test the hypothesis of the study. The sample of the study at three junior high schools in Paser City, representing high, medium and low school students.. The instruments used in this study were pre-post test, pre-post questionnaires, and observation. The data were analyzed using independent sample t-tests, paired sample tests, annova tests, and descriptive analysis. The findings of pre-post test and pre-post questionnaire analysis using t-test showed that there were significant differences in group mathematical communication skills using constructivism approach compared to groups using conventional approaches at all achievement levels of high school students (high, simple and low). Based on the observation, it is found that high achievement school students have good mathematical communication skills in mathematical communication, these are identified in many aspects and observation indicators achieved by students during learning.